What Influences MSMEs to Seek Credit? An Empirical Study at Bank BPD Kaltimtara Sebulu Sub Branch Office - Sailawati Sailawati; Eka Putri Aryanti; Noor Fachman Tjetje; Ching Yen Li (Politeknik Caltex Riau, 2026)
Main Purpose – The purpose of this study was to determine the influence of credit procedures, collateral, credit requirements, and interest rates on the decision to apply for MSME credit at Bank Kaltimtara KCP Sebulu. Method – This research used a quantitative research. The sampling technique in this study used a purposive sampling technique with 133 respondents as the sample. Data were collected through the distribution of questionnaires with Likert scale measurements. Data processing was carried out using using IBM SPSS Statistics software version 27. Main Findings – The results of this study indicate that partially the credit guarantee, credit requirements, and interest rate variables have a positive and significant effect on credit decisions, while the credit procedure variable does not have a positive and significant effect on credit decisions at Bankaltimtara. Simultaneously, the credit procedure, credit collateral, credit requirements and interest rate variables have a positive and significant effect on credit decisions at Bank BPD Kaltimtara Sebulu Sub-Branch office. Theory and Practical Implications – This study’s findings enrich the literature on credit decision-making among MSME, particularly regarding the credit procedure variable, which is shown to have no effect on their credit decision-making. This indicates that MSME actors do not consider credit procedures as a priority factor when making credit decisions at Bankaltimtara KCP Sebulu. Novelty – This study contributes by integrating the variables of credit procedures, credit collateral, credit requirements, and interest rates with the credit decisions of MSME in Sebulu District.